The Nature and Promise of Analytic Theology - Crisp, Oliver (Brill research perspectives in theology, 2019)
In the past decade analytic theology has established itself as a flourishing research program that includes academic journals, monograph series, a dedicated annual conference, research centers on several continents, and a growing and diverse body of work produced by scholars drawn from philosophy, theology, and biblical studies. In this short monograph Oliver Crisp, James Arcadi, and Jordan Wessling introduce readers to analytic theology. The work provides an account of analytic theology, some of the main areas in which analytic theologians have worked, and some of the prospects for the future of analytic theology going forward. It also addresses some key objections to analytic theology as a theological method, and aims to acquaint scholars and students with this new and promising theological movement.